The Influence of Good Governance and BUMN Business Collaboration on Competitive Advantage and Company Performance of the Indonesian Classification Bureau - Joustra Billy; Martani Huseini; Feriska Ajeng Anantri (International Journal of Economics Development Research (IJEDR), 2023)
PT Biro Classification Indonesia (Persero) which is abbreviated as BKI as the holding company for survey services (ID Survey) was appointed by the Geospatial Information Agency as the executor of basic geospatial implementation with a Cooperation scheme between the Central Government and BUMN. BKI is one of the BUMN engaged in survey services with classification and consulting service products. With government intervention and policies to improve company performance. PT BKI conducts business collaborations with its holding company and also with several other state-owned company networks. This study determines the effect of good governance and business collaboration on the competitive advantage and performance of Indonesian Classification Bureau companies. This study uses a quantitative method using SEM model analysis using the SmartPLS application. The results of this study provide that all independent variables in this study, namely the variables of good governance and business collaboration, have a positive and significant influence on the competitive advantage and performance of Indonesian Classification Bureau companies.